Perspectives for development of gluten-free products - Mukoid, Roman (My University, 2018)
The purpose of the work is to study the prospects for the development and use of gluten-free products

Метою роботи є дослідження перспективи розробки та використання безглютенових продуктів
Keywords: кафедра біотехнології продуктів бродіння і виноробства; grain; rice; beer; mashing; gluten-free raw material; зерно; рис; пиво; затирання; безглютенова сировина